Suffering a Healthy Life—On the Existential Dimension of Health - Binder, Per-Einar (Frontiers in psychology, 2022)
This paper examines the existential context of physical and mental health. Hans Georg Gadamer and The World Health Organization’s conceptualizations are discussed, and current medicalized and idealized views on health are critically examined. The existential dimension of health is explored in the light of theories of selfhood consisting of different parts, Irvin Yalom’s approach to “ultimate concerns” and Martin Heidegger’s conceptualization of “existentials.” We often become aware of health as an existential concern during times of illness, and health and illness can co-exist. The paper discusses how existential suffering in Western culture is described, to an increasing degree, as disorders or psychological deficits, and perfectionistic health goals easily can become a problem. We seek to avoid suffering rather than relate to it, with all the tension that may create. The paper argues that suffering is an unavoidable aspect of people’s experience of their lives, and actively relating to suffering must be regarded as a fundamental aspect of health. The need and usefulness of a concept of “existential health” is discussed.